Arbitrating Innovation: Navigating Arbitrability of Patent Disputes in the Indian Legal Landscape (Journal of Intellectual Property Rights (JIPR), 2025)
In 2018, the lengthy and high-profile patent infringement battle between smartphone titans Samsung and Apple concluded after seven years of extensive litigation, culminating in damages reaching millions of dollars. The considerable time taken to reach a decision could have been significantly reduced had arbitration been the chosen method for resolving the case. There is a growing interest in patent arbitration in many countries like U.S where patent disputes are expressly arbitrable. Despite this, the parties are confronted with major legal and practical obstacles to the use of arbitration, internationally and nationally. And then comes countries like India where, due to lack of legislation and public policy reasons, it is difficult to ascertain whether the dispute regarding patents are arbitrable or not. In this regard, this research paper discusses current framework on the arbitrability of patents disputes in India and also compares it with the legal framework of different countries in order to find some possible solutions to the existing uncertainty present in Indian laws with respect to arbitrability of patent disputes.